'Une vierge à soi-même enlacée': the cycle of the eternal return in Paul Valéry's La Jeune Parque - Hurst, Alastair (Spunti e Ricerche, 2016)
The presence of the human voice within La Jeune Parque, and that of its vocal correlative intonation, are crucial, and their semantic import, on all levels, is profound. La Jeune Parque is a poetic, if not operatic, dramatisation of certain characteristics and qualities of the human voice upon which Valéry had long reflected and meditated. In essence, La jeune Parque is a question to which no answer will be given, and from this absence or hollow inherent in the text springs the absolute centrality of intonation in this poem.